Health Systems Science Education: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
The National Academies Global Forum on Innovations in Health Professional Education held a public workshop in November 2023. Speakers explored how health professional educators and providers with health systems science (HSS) training can prepare learners to work together within health systems, resulting in better patient care, improved population health, and enhanced health professional well-being. Organizers hosted a public pre-workshop in October 2023 to create a foundational understanding of HSS prior to their workshop.

Training Physicians for Public Health Careers - Institute of Medicine (The National Academies Press, 2007)
Public health efforts have resulted in tremendous improvements in the health of individuals and communities. The foundation for effective public health interventions rests, in large part, on a well-trained workforce. Unfortunately there is a major shortage of public health physicians who are prepared to face today's public health challenges. Training Physicians for Public Health Careers focuses on the critical roles that physicians play in maintaining and strengthening the public health system, identifies what these physicians need to know to engage in effective public health actions, explores the kinds of training programs that can be used to prepare physicians for public health roles, and examines how these training programs can be funded. Medical schools, schools of public health, health care and public health care professionals, medical students and students of public health will find this of special interest.

Mental Health, Substance Use, and Wellbeing in Higher Education: Supporting the Whole Student - National Academies of Sciences, Engineering,; Medicine
Student wellbeing is foundational to academic success. One recent survey of postsecondary educators found that nearly 80 percent believed emotional wellbeing is a \

Supporting Black Students Through Their Science, Engineering, and Medicine Career Journeys: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
Increasing the number of Black men and Black women who enter the fields of science, engineering, and medicine (SEM) will benefit the social and economic health of the nation. On May 2-3, 2022 the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine of the National Academies of Sciences, Engineering, and Medicine convened a workshop to highlight promising financial and supportive services and programs throughout various stages of career development. Sessions followed student progression through the major stages of education and career development, and identified policies and practices that aim to mitigate and alleviate long-standing barriers to the full participation of Black students in SEM at the K201312, undergraduate, and graduate and professional levels.

Transforming the Financing of Early Care and Education - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
High-quality early care and education for children from birth to kindergarten entry is critical to positive child development and has the potential to generate economic returns, which benefit not only children and their families but society at large. Despite the great promise of early care and education, it has been financed in such a way that high-quality early care and education have only been available to a fraction of the families needing and desiring it and does little to further develop the early-care-and-education (ECE) workforce. It is neither sustainable nor adequate to provide the quality of care and learning that children and families need2014a shortfall that further perpetuates and drives inequality. Transforming the Financing of Early Care and Education outlines a framework for a funding strategy that will provide reliable, accessible high-quality early care and education for young children from birth to kindergarten entry, including a highly qualified and adequately compensated workforce that is consistent with the vision outlined in the 2015 report, Transforming the Workforce for Children Birth Through Age 8: A Unifying Foundation. The recommendations of this report are based on essential features of child development and early learning, and on principles for high-quality professional practice at the levels of individual practitioners, practice environments, leadership, systems, policies, and resource allocation.

Artificial Intelligence in Health Professions Education: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The National Academies Global Forum on Innovation in Health Professional Education hosted a multi-day workshop series in March and April 2023 to explore the potential of artificial intelligence (AI) in health professions education. Speakers at the workshops provided background on AI; discussed the social, cultural, policy, legal, and regulatory considerations to integrating AI into health care and training; considered the skills health professionals will need as educators and providers to effectively use AI in practice; and explored needs for educating the next generation of health workers. Speakers took consideration of the bias, burden, health equity concerns that introducing AI into clinical education would bring. This Proceedings of a Workshop summarizes the discussions held during the workshop.

Mentoring of Black Graduate and Medical Students, Postdoctoral Scholars, and Early-Career Faculty in Science, Engineering, and Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
On December 7 and 8, 2020, the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine of the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop that examined how to strengthen mentoring and advising of Black students and professionals in science, engineering, and medicine. Presenters included faculty deans, social scientists who are experts in organizational and professional development, and program implementers. Throughout the workshop, individual presenters highlighted evaluation criteria used by successful pipeline programs, including statistics on recruitment, retention, and advancement; career and leadership accomplishments; and awards and publications. This publication summarizes the presentations and discussions of the workshop.

A Framework for Educating Health Professionals to Address the Social Determinants of Health - Institute of Medicine; National Academies of Sciences, Engineering,; Medicine
The World Health Organization defines the social determinants of health as \

A Summary of the December 2009 Forum on the Future of Nursing: Care in the Community - Institute of Medicine (The National Academies Press, 2010)
The Robert Wood Johnson Foundation Initiative on the Future of Nursing, at the IOM, seeks to build a blueprint for the future of nursing as part of larger efforts to reform the health care system. The second of the Initiative's three forums was held on December 3, 2009, and examined care in the community, focusing on community health, public health, primary care, and long-term care.

Graduate Medical Education That Meets the Nation's Health Needs - Institute of Medicine (The National Academies Press, 2014)
Today's physician education system produces trained doctors with strong scientific underpinnings in biological and physical sciences as well as supervised practical experience in delivering care. Significant financial public support underlies the graduate-level training of the nation's physicians. Two federal programs2014Medicare and Medicaid2014distribute billions each year to support teaching hospitals and other training sites that provide graduate medical education. Graduate Medical Education That Meets the Nation's Health Needs is an independent review of the goals, governance, and financing of the graduate medical education system. This report focuses on the extent to which the current system supports or creates barriers to producing a physician workforce ready to provide high-quality, patient-centered, and affordable health care and identifies opportunities to maximize the leverage of federal funding toward these goals. Graduate Medical Education examines the residency pipeline, geographic distribution of generalist and specialist clinicians, types of training sites, and roles of teaching and academic health centers. The recommendations of Graduate Medical Education will contribute to the production of a better prepared physician workforce, innovative graduate medical education programs, transparency and accountability in programs, and stronger planning and oversight of the use of public funds to support training. Teaching hospitals, funders, policy makers, institutions, and health care organizations will use this report as a resource to assess and improve the graduate medical education system in the United States.

Assessing Health Professional Education: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Assessing Health Professional Education is the summary of a workshop hosted by the Institute of Medicine's Global Forum on Innovation in Health Professional Education to explore assessment of health professional education. At the event, Forum members shared personal experiences and learned from patients, students, educators, and practicing health care and prevention professionals about the role each could play in assessing the knowledge, skills, and attitudes of all learners and educators across the education to practice continuum. The workshop focused on assessing both individuals as well as team performance. This report discusses assessment challenges and opportunities for interprofessional education, team-based care, and other forms of health professional collaborations that emphasize the health and social needs of communities.

Improving Health Professional Education and Practice Through Technology: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
A pressing challenge in the modern health care system is the gap between education and clinical practice. Emerging technologies have the potential to bridge this gap by creating the kind of team-based learning environments and clinical approaches that are increasingly necessary in the modern health care system both in the United States and around the world. To explore these technologies and their potential for improving education and practice, the National Academies of Sciences, Engineering, and Medicine hosted a workshop in November 2017. Participants explored effective use of technologies as tools for bridging identified gaps within and between health professions education and practice in order to optimize learning, performance and access in high-, middle-, and low-income areas while ensuring the well-being of the formal and informal health workforce. This publication summarizes the presentations and discussions from the workshop.

A Summary of the October 2009 Forum on the Future of Nursing: Acute Care - Institute of Medicine (The National Academies Press, 2010)
The Robert Wood Johnson Foundation Initiative on the Future of Nursing, at the IOM, seeks to transform nursing as part of larger efforts to reform the health care system. The first of the Initiative's three forums was held on October 19, 2009, and focused on safety, technology, and interdisciplinary collaboration in acute care.

Envisioning the Future of Health Professional Education: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
In April 2015, the Institute of Medicine convened a public workshop to explore recent shifts in the health and health care industry and their implications for health professional education (HPE) and workforce learning. This study serves as a follow-up to the 2009 Lancet Commission report on health professions education for the 21st century and seeks to expand the report's messages beyond medicine, nursing, and public health. Envisioning the Future of Health Professional Education discusses opportunities for new platforms of communication and learning, continuous education of the health workforce, opportunities for team-based care and other types of collaborations, and social accountability of the health professions. This study explores the implications that shifts in health, policy, and the health care industry could have on HPE and workforce learning, identifies learning platforms that could facilitate effective knowledge transfer with improved quality and efficiency, and discusses opportunities for building a global health workforce that understands the role of culture and health literacy in perceptions and approaches to health and disease.

Future Financial Economics of Health Professional Education: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
An adequate, well-trained, and diverse health care workforce is essential for providing access to quality health care services. However, despite more than a decade of concerted global action to address the health workforce crisis, collective efforts are falling short in scaling up the supply of health workers. The resulting health workforce shortage affects people2019s access to quality health care around the globe. In October 2016, the National Academies of Sciences, Engineering, and Medicine convened a workshop to explore resources for financing health professional education in high-, middle-, and low-income countries and innovative methods for financially supporting investments in health professional education within and across professions. Participants examined opportunities for matching population health needs with the right number, mix, distribution, and skill set of health workers while considering how supply and demand drive decisions within education and health. This publication summarizes the presentations and discussions from the workshop.

The Future of Nursing: Leading Change, Advancing Health - Institute of Medicine (The National Academies Press, 2011)
The Future of Nursing explores how nurses' roles, responsibilities, and education should change significantly to meet the increased demand for care that will be created by health care reform and to advance improvements in America's increasingly complex health system. At more than 3 million in number, nurses make up the single largest segment of the health care work force. They also spend the greatest amount of time in delivering patient care as a profession. Nurses therefore have valuable insights and unique abilities to contribute as partners with other health care professionals in improving the quality and safety of care as envisioned in the Affordable Care Act (ACA) enacted this year. Nurses should be fully engaged with other health professionals and assume leadership roles in redesigning care in the United States. To ensure its members are well-prepared, the profession should institute residency training for nurses, increase the percentage of nurses who attain a bachelor's degree to 80 percent by 2020, and double the number who pursue doctorates. Furthermore, regulatory and institutional obstacles2014including limits on nurses' scope of practice2014should be removed so that the health system can reap the full benefit of nurses' training, skills, and knowledge in patient care. In this book, the Institute of Medicine makes recommendations for an action-oriented blueprint for the future of nursing.

Health Professions Education: A Bridge to Quality - Institute of Medicine (The National Academies Press, 2003)
The Institute of Medicine study Crossing the Quality Chasm (2001) recommended that an interdisciplinary summit be held to further reform of health professions education in order to enhance quality and patient safety. Health Professions Education: A Bridge to Quality is the follow up to that summit, held in June 2002, where 150 participants across disciplines and occupations developed ideas about how to integrate a core set of competencies into health professions education. These core competencies include patient-centered care, interdisciplinary teams, evidence-based practice, quality improvement, and informatics. This book recommends a mix of approaches to health education improvement, including those related to oversight processes, the training environment, research, public reporting, and leadership. Educators, administrators, and health professionals can use this book to help achieve an approach to education that better prepares clinicians to meet both the needs of patients and the requirements of a changing health care system.

Exploring the Role of Accreditation in Enhancing Quality and Innovation in Health Professions Education: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
The purpose of accreditation is to build a competent health workforce by ensuring the quality of training taking place within those institutions that have met certain criteria. It is the combination of institution or program accreditation with individual licensure2014for confirming practitioner competence2014that governments and professions use to reassure the public of the capability of its health workforce. Accreditation offers educational quality assurance to students, governments, ministries, and society. Given the rapid changes in society, health, and health care, the National Academies of Sciences, Engineering, and Medicine hosted a workshop in April 2016, aimed to explore global shifts in society, health, health care, and education, and their potential effects on general principles of program accreditation across the continuum of health professional education. Participants explored the effect of societal shifts on new and evolving health professional learning opportunities to best ensure quality education is offered by institutions regardless of the program or delivery platform. This publication summarizes the presentations and discussions from the workshop.

Redesigning Continuing Education in the Health Professions - Institute of Medicine (The National Academies Press, 2010)
Today in the United States, the professional health workforce is not consistently prepared to provide high quality health care and assure patient safety, even as the nation spends more per capita on health care than any other country. The absence of a comprehensive and well-integrated system of continuing education (CE) in the health professions is an important contributing factor to knowledge and performance deficiencies at the individual and system levels. To be most effective, health professionals at every stage of their careers must continue learning about advances in research and treatment in their fields (and related fields) in order to obtain and maintain up-to-date knowledge and skills in caring for their patients. Many health professionals regularly undertake a variety of efforts to stay up to date, but on a larger scale, the nation's approach to CE for health professionals fails to support the professions in their efforts to achieve and maintain proficiency. Redesigning Continuing Education in the Health Professions illustrates a vision for a better system through a comprehensive approach of continuing professional development, and posits a framework upon which to develop a new, more effective system. The book also offers principles to guide the creation of a national continuing education institute.

Improving Genetics Education in Graduate and Continuing Health Professional Education: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
Many health care providers do not have either the knowledge or the tools they need in order to apply genetic information in their day-to-day practices. This lack of support is contributing to a substantial delay in the translation of genetic research findings, when appropriate, into improvement in patient outcomes within the health care system. Although the need to improve genetics knowledge among health care providers is clear, the best approaches to educating health care providers in a way that produces meaningful changes in clinical practice are not, especially given the competing coursework and training needs that exist in today's increasingly complex health care settings. To examine the potential and the challenges of providing genetics education, the Roundtable on Translating Genomic-Based Research for Health of the Institute of Medicine hosted a workshop on August 18, 2014. The workshop examined a variety of approaches that could improve the teaching of genetics in the graduate and continuing education of health professionals; these approaches included online and interactive instruction, just-in-time approaches, the development of clinical decision-support tools, and the incorporation of genetics requirements into licensing and accreditation. This report summarizes the presentations and discussion of the event.